ASSOCIATIVE PLOT: GENESIS, THEORETICAL PARADIGM, AND LITERARY ANALYSIS (Scientific journal of the Fergana State University, 2026)
This article studies the genesis of the associative plot, the interaction of association with psychology, and the transition of association from psychology to other areas. The opinions and views of scientists regarding the associative plot, which is one of the main types of plot in literary criticism, are analyzed. The associative type of plot construction in Uzbek literature and its functions are analyzed using the example of U. Hamdam’s novel “Father”.